2017
DOI: 10.3389/fphys.2017.00879
|View full text |Cite
|
Sign up to set email alerts
|

Different Principles of ADP-Ribose-Mediated Activation and Opposite Roles of the NUDT9 Homology Domain in the TRPM2 Orthologs of Man and Sea Anemone

Abstract: A decisive element in the human cation channel TRPM2 is a region in its cytosolic C-terminus named NUDT9H because of its homology to the NUDT9 enzyme, a pyrophosphatase degrading ADP-ribose (ADPR). In hTRPM2, however, the NUDT9H domain has lost its enzymatic activity but serves as a binding domain for ADPR. As consequence of binding, gating of the channel is initiated. Since ADPR is produced after oxidative DNA damage, hTRPM2 mediates Ca2+ influx in response to oxidative stress which may lead to cell death. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 74 publications
1
19
0
Order By: Relevance
“…As a distantly related orthologue, the property of nvTRPM2 channel is different from human TRPM2 (hTRPM2). For example, the NUDT9 homology (NUDT9-H) domain in nvTRPM2 conserved the enzyme activity for catalyzing ADPR (Kühn et al, 2017). Although recent studies identified a calciumbinding site in the S2-S3 loop of nvTRPM2 that may be involved in the calcium-dependent regulation of the nvTRPM2 channel activity (Zhang et al, 2018), the underlying mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As a distantly related orthologue, the property of nvTRPM2 channel is different from human TRPM2 (hTRPM2). For example, the NUDT9 homology (NUDT9-H) domain in nvTRPM2 conserved the enzyme activity for catalyzing ADPR (Kühn et al, 2017). Although recent studies identified a calciumbinding site in the S2-S3 loop of nvTRPM2 that may be involved in the calcium-dependent regulation of the nvTRPM2 channel activity (Zhang et al, 2018), the underlying mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a loss of function phenotype for properly surface-expressed hTRPM2-∆NUD as well as a fully functional channel variant nvTRPM2-∆NUD with largely unaffected sensitivity to ADPR and additional sensitivity to hydrogen peroxide were identified [16]. The latter result revealed that ADPR-dependent activation of TRPM2 in principle can be accomplished independently of the NUDT9H domain and thus challenged the previously adopted standard hypothesis [59]. In addition to this main finding, further interesting results were obtained from these initial studies on nvTRPM2 as briefly summarized in the following:…”
Section: Paradigms Shifted-discovery Of a Novel Adpr-dependent Gatingmentioning
confidence: 95%
“…Extracellular NAD + is used as substrate by a series of receptors on cell membranes. For instance, TRPM2 (melastatin-like transient receptor potential 2 channel), a ligand-gated Ca 2+ -permeable nonselective cation channel, possesses a NUDT9 Homology Domain that is activated by ADP-Ribose, 2 -deoxy-ADPR and by ADP-ribose-2 -phosphate [49][50][51][52].…”
Section: Nicotinic Acid Adenine Dinucleotide Phosphate (Naadp) and Cymentioning
confidence: 99%